Surgical and Medical Management of Isolated Tricuspid Valve Infective Endocarditis in Intravenous Drug Users. Issue 2 (20th December 2015) - Shetty, Nabha; Nagpal, Dave; Koivu, Sharon; Mrkobrada, Marko
Abstract : Background: Tricuspid valve (TV) infective endocarditis (IE) is a known complication of intravenous drug use (IVDU). This study assessed long‐term outcomes of surgically and medically treated cases of TV IE. Methods: This was a retrospective cohort study of all cases of native TV IE treated in London, Ontario between 2008 and 2011. Outcomes for medically and surgically managed cases were assessed at two years. Outcomes related to the timing of surgery were also assessed. Results: Thirty‐eight patients were included; seven received valve surgery: five repairs, two replacements. All patients had a history of IVDU. Baseline characteristics were equal in both groups. Death at two years was 43% in the surgical group and 26% in the nonsurgical group (p = 0.522). In those who received surgery within 30 days versus after 30 days from admission, death was 33% and 50%, respectively (p = 1.00). No patients received emergent surgery (within seven days of admission). Twenty‐nine percent of the surgical group survived disease free versus 52% of the nonsurgical group. Survival with morbidity was mainly related to ongoing IVDU. The highest risk for mortality in both groups was ongoing IVDU. Conclusions: In IVDU‐related TV IE the highest risk for mortality appears to be ongoing IVDU and persistent or recurrent endocarditis. doi: 10.1111/jocs.12682 (J Card Surg 2016;31:83–88)